PENGARUH BRAND EQUITY, BRAND IMAGE, BRAND TRUST, PRICE, WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SEPATU MERK NIKE - Trya May Indriani; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to analyze the effect of brand equity, brand image, brand trust, price and word of mouth on the purchase decisions of Nike brand shoes. This type of research is a type of explanatory research using a quantitative approach. This research was conducted by distributing questionnaires to 80 respondents who were users of Nike brand shoes. The analysis technique used in this study is path analysis.The results of this study indicate that brand equity, brand image, brand trust and price have a positive and significant influence on purchasing decisionsKeywords: Brand Equity, Brand Image, Brand Trust, Price, Word Of Mouth and Purchasing Decision..